QUALITY OF LIFE OF ELDERLY PERSONS PLACED IN A NURSING HOME - Egeljic-Mihailovic, Natasa; Pavlovic, Jelena; Brkic-Jovanovi, Nina; Milutinovic , Dragana (HEALTH CARE, 2021)
Modern society in recent decades is facing a large increase in the share of people over 65 in the total population. The research shows that the trend of increasing the number of the elderly is such that it is estimated that the share of people aged 65 and over in the world population will increase significantly (by 56%), from 901 million (12.3%) in 2015 to 1.4 billion (16.5%) in 2030. Nursing homes for the accommodation and care of the elderly are safe places that provide the elderly with reduced physical and other abilities and a life worthy of a human being. A wide field of interest for the research is the perception and experience of home care users about what a quality life in this environment could represent. As part of the quality of life assessment, different domains are assessed, and a certain degree of subjective assessment is included in the choice of quality of life domains. Given the demographic changes that have led to an aging population, as well as longer life expectancy, new measures of social and health policy towards the elderly are increasingly aimed at raising the quality of life of the elderly, while scientific research is increasingly focused on identifying factors that affect the quality of life of the elderly.